A watchmaker's precision at high-pressure reveals CeCu 2 Si 2 and CeAu 2 Si 2 p-T phase diagrams - Pedrazzini, Pablo (2017)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina